Improved Profiles of Electron Density Distribution Along Collagen Fibrils - Chandross, Ronald J. (1973)
In order to evaluate fully the meaning of small-angle X-ray diffraction data from collagen fibers in terms of the distribution of molecular substance along fibrillar axes, it is necessary to have some means of determining the phase angles of the several components of the axial diffraction series for combination with measured amplitudes in the formulation of a Fourier series expressing the fibrillar electron density profile. This investigation has developed strip models for fibrillar axial structure based on reported electron micrographic descriptions of how stainable bands and molecular overlap zones (“backgrounds”) are located along the fibrils. These models permit the calculation of phases for use with the experimental amplitudes. Once band descriptions (identical widths and density heights plus relative locations) were fixed, three parameters dealing with background width, height, and location were varied to refine the models until they were reasonably capable of accounting theoretically for the observed diffraction amplitudes. Further minor adjustments, indicated by the initial results, finally produced models and profiles for dry and moist kangaroo tail tendon (KTT). The results show that the X-ray and electron optical conclusions regarding collagen fibrillar axial structure are in essential agreement down to a resolution of about 45 Å.